Adsorption Photocatalytic Removal of Rhodamine B using Dodecyl Dimethyl Betaine (BS12) Intercalated Silver Tetratungstate-Bentonite composites: Effect of Ag and Surfactant Loading, pH, and its Subsequent Economic Feasibility - Sumardiono, Siswo; Setiawan, Fajar Kasih; Jos, Bakti; Cahyono, Heri (Reaktor, 2025)
The potential of silver tetratungstate-doped bentonite intercalated with zwitterionic surfactant for removing Rhodamine B (RhB) was evaluated by comparing three composites, namely, AB (acid-activated bentonite), AB impregnated with Ag8W4O16 photocatalyst (Ag@AB), and Ag@AB intercalated with dodecyl dimethyl betaine (BS12) surfactant (Ag@OAB) with respect to their photocatalytic adsorption performance. The AB composite was prepared by treating natural bentonite with hydrochloric acid (HCl). Next, Ag@AB was synthesized by wet impregnation of Ag₈W₄O₁₆ onto AB. Lastly, the Ag@OAB was formed by intercalating the BS12 surfactant onto the Ag@AB composite. The morphology of the composite structures was characterized using Scanning Electron Microscopy (SEM). The addition of 4% Ag (w/w) tetratungstate W4O16 and 50% CEC BS12 to AB produced RhB removal percentages of 66% and 59%, respectively, compared to 65% for AB. The maximum removal percentage was achieved at pH 4 for the AB, Ag@AB, and Ag@OAB composites with RhB removal percentages of 67%, 71%, and 44%, respectively. The AB composite showed the highest regenerative ability compared to Ag@AB and Ag@OAB, with AB maintaining RhB removal at 70% after five regeneration cycles, while Ag@AB and Ag@OAB only reached four and three regeneration cycles. The total production cost of AB is fourteen to sixteen times lower than that of Ag@AB and Ag@OAB composites. In summary, the impregnation of the Ag₈W₄O₁₆ photocatalyst onto AB, resulting in the Ag@AB composite, increases the RhB removal efficiency compared to pristine AB. In contrast, the intercalation of the BS12 surfactant in Ag@OAB composite led to a decrease in RhB removal efficiency, resulting in the lowest performance among the three composites.